ANALISIS KUALITAS PRODUK DAN BRAND IMAGE SERTA LIFE STYLE TERHADAP KEPUTUSAN PEMBELIAN PRODUK J.REP DI KOTA SAMARINDA - DIAH AMARATANI; SYARIFAH HUDAYAH; SRI WAHYUNI (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The research was conducted at PT. Seraphim Karya Agung is one store J.REP in the city Samarinda. The data was collected through observasion, interview, questionnaires and literature study the was selected through systematically method based on objective research. The result werw analyzed using multiple linier regression analysis, using the t test as hypothesis examination. The used the correlation calculation to determine the influence and significance of product quality, brand image and Life style on product purchasing decision in J.REP Samarinda. The result of this research showed that product quality, brand image and Life style on product purchasing decision in J.REP Samarinda. The equation obtained is U = - 1,682 + 0,318x1 +0,317x2 +0,383x3, means that variables of product quality, brand image and Life style on product purchasing decision have a positive impact on consumer purchasing decisions. The result that based on statistical test that product quality, brand image and Life style on product purchasing decision  have a positive impact on purchasing decisions variables. Values obtained from this study is Adjusted R Square of 0,276. This result indicated that 27,6% consumer purchase decision on the purchase of product J.REP in Samarinda is influenced by variation of the three independent variables, product quality, brand image and Life style. The remaining balance of 72,4% influenced by other variables that had not been examined.Keywords: product quality, brand image and Life style